HTLV-1 and HIV-1 co-infection: A case report and review of the literature. (2016) - Isache, Carmen; Sands, Michael; Guzman, Nilmarie; Figueroa, Danisha
Abstract: HTLV type 1 and 2 are both involved in actively spreading epidemics, affecting over 15 million people worldwide. HTLV-1 has been described as the more clinically significant one, being associated with diseases such as adult T-cell leukemia and tropical spastic paraparesis. We report here a case of tropical spastic paraparesis in an HIV-positive patient who did not report any history of travel or residence in an HTLV endemic area. A 57 year old African-American male was admitted to the hospital due to bilateral upper and lower extremity weakness associated with stiffness. He had recently been diagnosed with HIV. His physical examination showed mild to moderate decreased motor strength, in both upper extremities and marked loss in both lower extremities. This was associated with hyperreflexia and clonus. Sensory function was intact. He looked cachectic and had several psoriatic plaques on both lower and upper extremities. Laboratory work-up showed a CD4 count decreased to 94 cells/mm 3 and a HIV viral load of 273, 000 copies/mL. Based on serum positivity for HTLV type 1 and the patient's clinical presentation suggestive of upper and lower motor neuron dysfunction, the diagnosis of tropical spastic paraparesis was made. HTLV and HIV share the same routes of transmission and the same tropism for T-lymphocytes. Co-infection occurs probably more frequently than we are aware, since testing for HTLV is not routinely performed in outpatient HIV clinics.